Undergraduate Teaching in Geriatrics and Pediatrics in Portuguese Medical Schools: An Observational Study - Amaral, Mariana (2016)
Introduction: Motivated by the contracting nature of the Portuguese age pyramid, and thereby the ever increasing geriatric population, the aim of this study was to compare the number of European Credit Transfer and Accumulation System Credits dedicated to Geriatrics with Pediatrics in Portuguese Medical Schools.Material and Methods: An observational, descriptive and cross-sectional study was conducted and included six Portuguese Medical Schools that have six years of training and a total of 360 credits. The study plans were obtained from the medical schools’ websites or requested. Schools were grouped in modular/classic teaching methodology and the courses were categorized in mandatory/optional and specific/related. The credits of Geriatrics and Pediatrics were compared.Results: Four schools had classical methodology and two had a modular one. Overall, they had more credits dedicated to Pediatrics than Geriatrics. Three schools offered mandatory courses specifically oriented to Geriatrics (1.5 - 8 credits) compared to all schools mandatory courses courses on Pediatrics (5.7 - 26.5 credits). The ratio of averages of mandatory specific courses (Pediatrics/Geriatrics) was 12.4 in the classical and 1.5 in the modular group.Discussion: Pediatrics teaching has revealed to be superior to Geriatrics in all categories. Based on our results, we consider the Portuguese Geriatrics’ undergraduate teaching sub-optimal.Conclusion: Nowadays, geriatric population is quantitatively similar to pediatric population. Efforts should be made to adequate Geriatrics teaching to our reality in order to provide a more adequate health care to this age group.